The Repurposing of Anti-Psychotic Drugs, Quetiapine and Olanzapine, as Anti-Cryptococcus Drugs - Ogundeji, Adepemi O.; Pohl, Carolina H.; Sebolai, Olihile M. (Frontiers in Microbiology, 2017)
The management of cryptococcal infections is often difficult. This can, in part, be attributed to the fungistatic nature of fluconazole, which may result in cells disseminating to give rise to pathogen-emergent psychosis following brain inflammation. This chance at treatment failure has necessitated the current study wherein the antimicrobial quality of anti-psychotic drugs viz. quetiapine and olanzapine, was assessed. The response of test strains towards quetiapine or olanzapine alone and in combined therapy with fluconazole or amphotericn B was measured. In addition, the mode of action of the two anti-psychotic drugs in killing cryptococcal cells was determined. At the end, the ability of these anti-psychotic drugs to chemo-sensitise macrophages was also examined. The assessed strains were shown to be susceptible to the two anti-psychotic drugs, which possibly killed them via altering their membrane function. Additionally, these anti-psychotic drugs acted in synergy with fluconazole and amphotericin B in controlling the growth of the test strains. Importantly, these drugs improved the phagocytic efficiency of macrophages and, at the same time, stimulated them to produce pro-inflammatory cytokines (interleukin 6 and interferon gamma), said to be critical in the clearance of cryptococcal cells. The minimum inhibition concentration of each anti-psychotic drugs was calculated to be within its respective recommended therapeutic range. This study’s findings highlight the potential clinical application of quetiapine and olanzapine as alternative anti-Cryptococcus drugs, which can be used to manage the fungal burden (infection) as well as the associated symptom (psychosis).